Subtitling’s a carnival’: New practices in cyberspace - Cintas, Jorge Diaz (The Journal of Specialised Translation, 2018)
In recent years, scholarly research in audiovisual translation in general, and subtitling in particular, has moved beyond the analysis of linguistic minutiae to embrace wider socio-cultural concerns, thus highlighting its societal significance and establishing closer links with film and media studies. In this article I set to explore the social significance of some of the new forms of subtitling that have surged in the age of digital media, thanks to the opportunities offered by the affordabilities and democratisation of technology. Drawing primarily on Bakhtin's theory of carnival, the discussion centres on how participatory subtitling activities warrant the pursuit of individual freedom and contribute to the breakdown of hegemony. The way in which these novel subtitling practices give voice to certain collectives whilst also challenging traditional information dissemination mechanisms is also probed.